Computational quest for finding potential Ebola VP40 inhibitors: a molecular docking study = [pencarian pengiraan untuk mencari potensi perencat Ebola VP40: suatu kajian mengedok molekul] - Mohamad Yussoff, Mohamad Ariff; Abdul Hamid, Azzmer Azzar; Abd Hamid, Shafida; Abd Halim, Khairul Bariyyah (Penerbit Universiti Kebangsaan Malaysia, 2020)
Interaction of Ebola virus matrix protein VP40 with RNA is crucial in the early infection stage to facilitate the transcription of the viral gene. Thus, VP40 is a promising target to inhibit the Ebola virus from spreading. This study aims to identify and optimize ligands that can potentially block the VP40-RNA binding site. A total of 42 compounds from previously studied ligands from the literature were simulated against the RNA binding site using Autodock Vina. The top ten ligands were used as templates for similarity search in ZINC database followed by structured-based virtual screening. Then, the ADME properties of the top compounds were predicted computationally using SwissADME server. Our results showed that Q-96 (ZINC ID: 1338855) is the best docked compound with binding free energy of -7.5 kcal/ mol. The compound also has satisfactory ADME properties prediction with good lipophilicity value, moderate water solubility and high gastrointestinal absorption. Besides, this ligand does not violate any drug likeness rules as well as no PAINS and Brenk alerts, indicate it has the properties as a drug. Thus, it is worth to carry out further investigations on this structure more in silico as well as in vitro and in vivo levels towards finding the treatment for Ebola virus disease. © 2020 Penerbit Universiti Kebangsaan Malaysia.